Flea and tick products and your pet - Skoglund, L. G., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet covers insecticides and other compounds used for flea control, symptoms of pesticide poisonings, what to do if pesticide poisoning occurs, and what should be included in a pet first aid kit.
CEPEP 5/00, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pets -- Safety measures; Fleas -- Control; Ticks -- Control; Pesticides -- Environmental aspects